Issues of Cyber security and its solutions in Nepalese Context (NPRC Journal of Multidisciplinary Research, 2024)
In today's digital age, the internet's expansion has brought great convenience but also raised cyber threats. So, identify the issue of cyber-security and its solution in Nepalese context is significant. Descriptive design and qualitative methods were employed, with data sourced from Google Scholar and analyzed through thematic analysis. The study shows a myriad of issues stemming from inadequate cyber security awareness in Nepal, including increased vulnerability to cyber-attacks, data breaches, and societal, economic, and regulatory consequences. Bridging the gap in cyber security awareness is imperative to mitigate risks effectively and foster a secure digital environment in Nepal. Strategies emphasizing education, training, and regulatory frameworks are vital for addressing these challenges and promoting technological advancement and societal trust. This study proposes AI-driven solutions to address the lack of cyber security awareness in the Nepalese context, offering a unique approach to mitigate cyber threats and foster a secure digital environment.